The Morals of Marc Chagall - (:unkn) unknown (My University, 2013)
This exhibition catalog presents a selection of illustrated book suites by Marc Chagall, a twentieth-century European artist. In presenting the print suites Dead Souls, The Fables of La Fontaine, and The Story of the Exodus, this exhibition highlights the subject of morality as defined by the images and experiences of Marc Chagall. The three texts comment overtly on morality in various ways, and Chagall's attitude regarding the morality depicted in these texts displays both personal and historical experiences. The themes and iconography chosen by Chagall for each illustrated book also reflect the experiences of his life. Chagall's intention in depicting each text was to show the moral stature of each character, and not to dictate morality or correct immoral behavior. In the end, it was not "moral" versus "immoral" that Chagall was interested in depicting, but the essentials of the human experience.
Keywords: Dead Souls; Fables of La Fontaine; Marc Chagall; Story of the Exodus